2014
DOI: 10.4103/1119-3077.144399
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of timely initiation of complementary feeding among children aged 6-24 months in Sagamu, Nigeria

Abstract: Complementary feeding is most frequently initiated earlier than 6 months in this population. Good breastfeeding practices may influence timely initiation of complementary feeding. Interventions should be targeted at the entire population irrespective of educational and socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
(22 reference statements)
1
30
5
Order By: Relevance
“…Compared to the current finding, a lower prevalence of timely initiation of complementary feeding was reported from Nigeria (41 %) [13] and India (55.7 %) [12]. This discrepancy could be attributed to differences in sample sizes between the two study areas, as more mothers were surveyed in India than in this study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Compared to the current finding, a lower prevalence of timely initiation of complementary feeding was reported from Nigeria (41 %) [13] and India (55.7 %) [12]. This discrepancy could be attributed to differences in sample sizes between the two study areas, as more mothers were surveyed in India than in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…In this regard, about 71 %, 70 %, 55 %, and 39 % of the infants in Bangladesh, Nepal, India, and Pakistan, respectively, are reported to have timely initiation of complementary feeding [8, 10–12]. On the other hand, there is a low rate of timely initiation of complementary feeding in Africa [1, 13]. In Ethiopia, more than half (57 %) of the child mortality occurs mainly due to undernutrition [14], and the majority of the children have had sub-optimal feeding practices.…”
Section: Introductionmentioning
confidence: 99%
“…Benin, Ghana and Guinea-Bissau were countries where the timely introduction of CFs was better, with proportions of children 6 to 8 months old having been introduced CFs estimated beyond 70%. A study on Nigerian children found that 53.8% had premature initiation of CF while 5.1% had delayed initiation of CF [14]. Other studies, in Mali and Senegal, revealed early introduction of CFs as a poor infant feeding practice [15,16] .…”
Section: Complementary Feeding Practices In West African Countries Timentioning
confidence: 99%
“…It appears that suboptimal complementary feeding practices remain one of the major causes of child malnutrition and mortality in West Africa [17]. Concerning the time of initiation of complementary feeding, complementary foods introduced too early or too late was the main impediment to exclusive breastfeeding (EBF) [14]. The inappropriate age of introduction of CFs remains a challenge that significantly hampers optimal child growth and development.…”
Section: Complementary Feeding Practices In West African Countries Timentioning
confidence: 99%
See 1 more Smart Citation